An Analysis of Derivational Morphology in Angelina Jolie’s UN Speech on Equality for Women - Meidi Kulsum, Eva; Halimatus Sadiah, Alviani (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to discuss derivational affixes in Angelina Jolie’s speech at the UN on women’s equality. This study uses a descriptive qualitative method in analysing the derivation words in Angelina Jolie's speech. The results found 78 derivation words, which consist of 16 prefixes (e.g. -in-, -re-, -epi-) and 62 suffixes (e.g -ity-, -ment-. -tion-). Prefixes are used to create a new meaning of the base word without changing the word class such as the prefix -in- on the word inequal and prefix -un- in the word unwilling the other hand, the addition of suffixes to the base word often changes the word class. A significant change is the change in verbs or adjectives into nouns as much as 73.3% when suffixes are added to verb or adjective base words such as the example of the word govern becomes government. The other change from noun to adjective is 20% as in the word politics becomes political last change of adjective to adverb as much as 6.7% as in the word peaceful becomes peacefully. The findings show a pattern of word formation through the derivational process that emphasizes its role in modifying meaning and grammatical function in the context of formal speech.